2018
DOI: 10.1136/bjophthalmol-2017-311360
|View full text |Cite
|
Sign up to set email alerts
|

Leap forward in the treatment of Pythium insidiosum keratitis

Abstract: We report favourable but not statistically significant response of keratitis to antibacterial agents in a pilot series of patients. Further evaluation of this strategy in larger number of patients is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(122 citation statements)
references
References 13 publications
4
117
0
1
Order By: Relevance
“…Patients with Pythium keratitis usually present with typical clinical manifestations, including multiple, linear, tentacle-like infiltrates and dot-like or pinhead-shaped infiltrates, involving the subepithelial, anterior stromal, and midstromal layers in surrounding cornea and radiating in a reticular pattern from the central area of the lesion towards the limbus (Fig. 3) (Lekhanont et al, 2009;Lelievre et al, 2015;Bagga et al, 2018;Chatterjee & Agrawal, 2018;Agarwal et al, 2019;He et al, 2016;Thanathanee et al, 2013;Sharma et al, 2015;Agarwal et al, 2018). Radial keratoneuritis has been observed in some cases (Lekhanont et al, 2009;He et al, 2016).…”
Section: Ocular Pythiosismentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with Pythium keratitis usually present with typical clinical manifestations, including multiple, linear, tentacle-like infiltrates and dot-like or pinhead-shaped infiltrates, involving the subepithelial, anterior stromal, and midstromal layers in surrounding cornea and radiating in a reticular pattern from the central area of the lesion towards the limbus (Fig. 3) (Lekhanont et al, 2009;Lelievre et al, 2015;Bagga et al, 2018;Chatterjee & Agrawal, 2018;Agarwal et al, 2019;He et al, 2016;Thanathanee et al, 2013;Sharma et al, 2015;Agarwal et al, 2018). Radial keratoneuritis has been observed in some cases (Lekhanont et al, 2009;He et al, 2016).…”
Section: Ocular Pythiosismentioning
confidence: 99%
“…Potential risk factors for pythiosis include farming exposure, direct contact with a water resource (i.e., lake, river, lagoon, swamp, or even swimming pool), and a history of travel to endemic countries, such as Thailand (Krajaejun et al, 2006b;Lelievre et al, 2015;Hasika et al, 2019;Appavu, Prajna & Rajapandian, 2019). Inappropriate hygiene of contact lens can pose a risk (Lekhanont et al, 2009;Lelievre et al, 2015;Badenoch et al, 2001;Maeno et al, 2019;Bernheim et al, 2019;Tanhehco et al, 2011;Barequet, Lavinsky & Rosner, 2013;Neufeld et al, 2018;Raghavan et al, 2018), and exposure to dust or some foreign body in their eyes (Bagga et al, 2018;Hasika et al, 2019) predisposes individuals with no agricultural activity to this infection. The incidence of pythiosis follows a seasonal trend (Hasika et al, 2019;Thanathanee et al, 2013) with outbreaks of Pythium keratitis occurring during the rainy season in Thailand (Thanathanee et al, 2013) and around June to September during monsoon season in South India (Hasika et al, 2019).…”
Section: Environmental (Extrinsic) Factorsmentioning
confidence: 99%
“…Data on the epidemiology of pythiosis is limited. Since the rst case in 1985, human pythiosis has been increasingly reported from all over Thailand [2,10,[13][14][15][16][17][18][19], where P. insidiosum is ubiquitous in the environment [3,4]. A seroprevalence study estimated that ~32,000 Thai people have been exposed to the pathogen [20].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, patients without complete surgical resection or patients with persistently elevated post-surgical (1,3)-β-D-glucan (BG) have not survived longer than 3 months, despite treatment with antifungal agents and immunotherapy (Worasilchai et al, 2018). The potential activity of antibacterial agents such as azithromycin, clarithromycin, and doxycycline against Pythium insidiosum has been demonstrated in in vitro studies (Loreto et al, 2011;Jesus et al, 2014) and animal models (Loreto et al, 2019;Jesus et al, 2015a), and more recently, successful therapy in ocular pythiosis has been reported (Bagga et al, 2018). Therefore, oral bacterial agents, in conjunction with antifungal agents, were administered in two patients with relapsed vascular pythiosis.…”
Section: Introductionmentioning
confidence: 99%